1997
DOI: 10.1016/s0041-1345(96)00554-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of donor hematopoietic progenitor cells after allogeneic liver transplantation

Abstract: The persistence of multilineage microchimerism after solid organ transplantation suggests long-lasting engraftment of donor hematopoietic progenitor cells (HPCs) originated from the transplanted organs. This study describes a method developed to identify donor HPCs in the recipient bone marrow and reports preliminary results obtained after allogeneic liver transplantation. METHODS Inbred male Lewis (LEW) and Brown Norway (BN) rats were used for experiments. Plastic dish nonadherent bone marrow cells (BMC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…BD, bile duct; HA, hepatic artery; HMS, hepatic microcirculatory unit; PV, portal vein. Constant exposure to intestinal microbial products fosters a “tolerogenic” microenvironment with relatively low co‐stimulatory and MHC class II expression on antigen presenting cells (APC), including the endothelium . Sinusoids are the majority microvasculature, lined by liver sinusoidal endothelial cells (LSEC) and Kupffer cells (KC) , which scavenge particulates/antigens, and regulate immune responses , liver regeneration , and fibrogenesis . Tremendous parenchymal regenerative abilities include collagenase‐mediated matrix remodeling , which can reverse fibrosis after elimination of immune injury. This is not observed with other solid organ allografts . A variety of immune leukocytes (classical T and B cells, natural killer [NK], NK T cells [NKT], and γδ‐T cells ) are normal hepatic inhabitants, including hematopoietic stem cells .…”
Section: Important Differences Between Liver and Other Solid Organ Almentioning
confidence: 99%
“…BD, bile duct; HA, hepatic artery; HMS, hepatic microcirculatory unit; PV, portal vein. Constant exposure to intestinal microbial products fosters a “tolerogenic” microenvironment with relatively low co‐stimulatory and MHC class II expression on antigen presenting cells (APC), including the endothelium . Sinusoids are the majority microvasculature, lined by liver sinusoidal endothelial cells (LSEC) and Kupffer cells (KC) , which scavenge particulates/antigens, and regulate immune responses , liver regeneration , and fibrogenesis . Tremendous parenchymal regenerative abilities include collagenase‐mediated matrix remodeling , which can reverse fibrosis after elimination of immune injury. This is not observed with other solid organ allografts . A variety of immune leukocytes (classical T and B cells, natural killer [NK], NK T cells [NKT], and γδ‐T cells ) are normal hepatic inhabitants, including hematopoietic stem cells .…”
Section: Important Differences Between Liver and Other Solid Organ Almentioning
confidence: 99%
“…126 Passenger liver hematopoietic cells 126,127 migrate to the bone marrow after liver transplantation and may establish persistent hematolymphopoietic chimerism. [128][129][130] In experimental models, the syngeneic parenchymal environment of the liver allograft appears to constitute a privileged site for persistent progenitor donor hematopoietic cells. 131 Some studies have also shown that hepatic oval cells and hematopoietic stem cells share CD34, Thy-1, and C-kit mRNA and protein.…”
Section: Bone Marrow Cells In the Livermentioning
confidence: 99%
“…The adult liver contains HSCs 93,94 and may serve as a major site of extramedullary hematopoiesis 93 . Passenger liver hematopoietic cells 95,96 migrate to the bone marrow after liver transplantation and may establish persistent hematolymphopoietic chimerism 97–99 . In experimental models, the syngeneic parenchymal environment of the liver allograft appears to constitute a privileged site for persistent progenitor donor hematopoietic cells 100 .…”
Section: Bone Marrow Cells In the Livermentioning
confidence: 99%